The Canada Student Loans Program: Time for Revision - Schaafsma, Joseph (Canadian Journal of Higher Education, 1990)
This paper consists of a critical appraisal of a number of aspects of the Canada Student Loans (CSL) program. In the first part of the paper it is argued that the current CSL program lacks horizontal and vertical equity and creates a work-disincentive. Furthermore, it is shown that the program rules are badly in need of up-dating to take into account the effects of inflation and tax rate increases since 1982. In the second part of the paper it is argued that the government is controlling the cost of the CSL interest subsidy inefficiently. An alternative design fro the CSL program is proposed and it is argued that this new design benefits both students and parents at little or no additional cost to the government.